Aproximaciones interpretativas al tratamiento informativo de la prensa durante la violencia política en Huancayo - Villanueva Basilio, Elvis (2021)
This article provides some approaches to study the written press during political violence in central part of Peru, specifically in the province of Huancayo. This study focused on three much talked-about cases of political violence occurred in 1986 and 1989 in Huancayo, the same ones that were commented on the Report of the Truth and Reconciliation Commission of Peru. Then, the information treatment given to these cases by the local newspapers Correo and La Voz de Huancayo was analyzed. It was found that these newspapers offered an informative treatment that was characterized by sensationalism, politicization, informative imprecision, and the scant exercise of journalistic investigation.